Reconstructing Islamic Religious Education in The Global Era: Addressing The Challenges of Digitalization and Radicalism in Indonesia - Fadhilah Husna Nurbaiti; Samia Novera; Erba Rozalina Yulianti; Alfi Lutfiyah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
The development of digital technology in the global era has brought about significant changes in the education system, including Islamic Religious Education (IRE). On the one hand, digitalization provides easy access to information and religious learning resources; on the other hand, it also presents various challenges, such as a shift in scholarly authority, low digital literacy, and the increasing spread of radical ideologies through social media. These conditions indicate that PAI education in Indonesia still faces problems in the form of a dominance of cognitive and formalistic approaches, as well as a weak internalization of religious values in the social lives of students. This study aims to analyze the dynamics and challenges of Islamic Religious Education in the global era and to formulate a relevant reconstruction of Islamic Religious Education to address digitalization and radicalism in Indonesia. This study employs a qualitative approach using library research methods. Data were collected from various books, scientific journals, articles, and academic sources related to Islamic Religious Education, digital literacy, religious moderation, and digital radicalism. Data analysis techniques were conducted through data reduction, categorization, interpretation, and drawing conclusions in a descriptive-analytical manner. The results of the study indicate that the reconstruction of Islamic Religious Education (PAI) needs to be directed toward the development of a critical, contextual, and moderate learning paradigm through the integration of digital literacy, the strengthening of religious moderation, the development of a critical religious mindset, and the transformation of the teacher’s role as a learning facilitator in the digital era. Furthermore, a learning approach based on reflection, dialogue, and critical thinking is essential in shaping students who are religious, tolerant, and adaptable to the changing times. Thus, Islamic Religious Education serves not only as a means of transferring religious knowledge but also as an ideological bulwark in confronting the challenges of digitalization and radicalism in Indonesia. Keywords: Islamic Religious Education, digitization, digital literacy, religious moderation, radicalism.